Analisis Manajemen Program Bahasa Arab Metode Mustaqili di Lembaga Kursus Pondok Pesantren Miftahul Huda Gading Malang - Ichwani, Imron; Rahmayanti, Indah; Kholid, Nur; Arifa, Zakiya (CV. Creative Tugu Pena, 2023)
TThis research examines the intensive Arabic language course program using the Mustaqilli method which is implemented at the Miftahul Huda Islamic Boarding School. Researchers use qualitative research methods, namely observation, documentation, and interviews to collect data by data reduction, data presentation, and conclusions that involve data analysis. This research uses qualitative descriptive techniques. The research results show that the management of the intensive Arabic language course program using the Mustaqilli method has been implemented successfully, including the implementation of management tasks such as planning, organizing, mobilizing and supervising as well as implementing program management. The success of this program is based on the cooperation of the mentors and students in implementing each component of the course program. Students who actively practice Arabic sentence construction in all language domains receive primary emphasis in Mustaqilli's approach to Arabic language teaching. Students are also increasingly active in speaking practice both inside and outside the classroom. Although there are still some shortcomings in its implementation, these are mainly related to time management and user needs.